Pressure Bearing Device Affects Extraction Socket Remodeling of Maxillary Anterior Tooth. A Prospective Clinical Trial. (18th August 2016) - Jiang, Xi; Zhang, Yu; Chen, Bo; Lin, Ye
Abstract: Background: Extraction socket remodeling and ridge preservation strategies have been extensively explored. Purpose: To evaluate the efficacy of applying a micro‐titanium stent as a pressure bearing device on extraction socket remodeling of maxillary anterior tooth. Materials and Methods: Twenty‐four patients with a extraction socket of maxillary incisor were treated with spontaneous healing (control group) or by applying a micro‐titanium stent as a facial pressure bearing device over the facial bone wall (test group). Two virtual models obtained from cone beam computed tomography data before extraction and 4 months after healing were 3‐dimenionally superimposed. Facial bone wall resorption, extraction socket remodeling features and ridge width preservation rate were determined and compared between the groups. Results: Thin facial bone wall resulted in marked resorption in both groups. The greatest palatal shifting distance of facial bone located at the coronal level in the control group, but middle level in the test group. Compared with the original extraction socket, 87.61 ± 5.88% ridge width was preserved in the test group and 55.09 ± 14.46% in the control group. Conclusions: Due to the facial pressure bearing property, the rigid micro‐titanium stent might preserve the ridge width and alter the resorption features of extraction socket.